Kombinasi Algoritma OTP Cipher dan Algoritma BBS dalam Pengamanan File - Tomoyud S. Waruwu; Kristian Telaumbanua (Jurnal SIFO Mikroskil, 2016)
Cryptography is the science of disguising messages so that only well known by the provider and the recipient. One algorithm that is sufficiently secure and difficult to solve is the one-time pad cipher algorithm. However, this algorithm is very dependent on the randomness of the key used and the key is only used one time only. blum blum shub algorithm is an algorithm to generate good random numbers ??? and difficult to predict. the combination of these two algorithms are expected to create more and better data security and guaranteed.